Correction of iron deficiency anemia in patients with obstetric and gynecological pathology (pharmacoeconomic comparative analysis) - Yu.E. Dobrokhotova; Markova E. A. (LCC «Medicine-Inform», 2018)
Correction of iron deficiency anemia in patients with obstetric and gynecological pathology (pharmacoeconomic comparative analysis) Dobrohotova Yu.E., Markova E. A. Pirogov Russian National Research Medical University, Moscow The authors provide a systematic comparative analysis of data on the clinical and cost effectiveness of ferrous iron preparation (Tardyferon®, Pierre Fabre Medicament Production, France) and its analogues and preparations of ferric iron in the treatment of iron deficiency anemia (IDA) in patients in obstetric and gynecological practice. The review of foreign and Russian articles, published in Pubmed over the past 15 years, is given. Modern data on the comparative effectiveness of iron preparations for the correction of IDA with their clinical and pharmacoeconomic evaluation are presented. Ferrous iron (ferrous sulfate) with retarded release (Tardyferon®, Pierre Fabre Medication Production, France) has a more pronounced effect on the dynamics of hematological parameters in comparison with its analogues and ferric iron preparations. Pharmacoeconomic analysis showed the advisability of using ferrous iron with retarded release for the correction of IDA in patients with obstetric and gynecological pathology. The optimal ratio of efficiency, price, availability, convenience  of the drug regimen ensures a high compliance of patients to the treatment, which allows achieving high clinical results in the treatment of IDA. Key words: pharmacoeconomic analysis, iron deficiency anemia, iron preparations, pregnancy, iron deficiency, Tardyferon. For citation: Dobrohotova Yu.E., Markova E.A. Correction of iron deficiency anemia in patients with obstetric and gynecological pathology (pharmacoeconomic comparative analysis) // RMJ. 2018. № 2(I). P. 29-33.